Effects of neuromuscular training on athletes physical fitness in sports: A systematic review - Akbar, Saddam; Soh, Kim Geok; Jazaily Mohd Nasiruddin, Nasnoor; Bashir, Marrium; Cao, Shudian; Soh, Kim Lam (Frontiers in Physiology, 2022)
Objective: This review study aimed to assess the impact of neuromuscular training (NT) on athletes’ physical fitness in sports. Methods: Three independent reviewers conducted a literature search in various databases: EBSCOHOST, PubMed, WOS, Scopus, ProQuest, Science Direct, additional references, and Google Scholar. The methodological quality was examined using Lubans’ predetermined methods, and data that included trials were excluded. Results: This review included 18 well-conducted systematic studies from 144 relevant publications. These studies were reviewed and have been given a score of 6. Medium-risk studies were scored 3 or 4, while low-risk studies were scored 5 or 6. None of the studies had a high-risk bias. The neuromuscular training intervention revealed that balance (n = 10) was the main characteristic of physical fitness that was evaluated, followed by agility (n = 6), muscular strength (n = 4), speed (n = 5), endurance, and muscular power (n = 2). Subsequently, most studies used an intervention such as plyometric and strength training exercises to improve agility, balance, and muscular strength among athletes. Conclusion: This review implicated that neuromuscular training (NT) focuses on exercises that enhance motor skills which aid athletes in moving their bodies according to their situational needs. The athletes’ slower and faster directions influence their agility, muscular strength, and balance, essential for player performance. It is recommended for future research to investigate the effects of NT on other physical fitness components (flexibility, cardiovascular endurance, cardiorespiratory endurance, body composition, and power) that are essential for athletes of all ages and gender.